Moving-wire device for carbon isotopic analyses of nanogram quantities of nonvolatile organic carbon - Sessions, A. L.; Sylva, S. P.; Hayes, J. M. (Anal Chem, 2005)
We describe a moving-wire analyzer for measuring 13C in dissolved, involatile organic materials. Liquid samples are first deposited and dried on a continuously spooling nickel wire. The residual sample is then combusted as the wire moves through a furnace, and the evolved CO2 is analyzed by continuous-flow isotope ratio mass spectrometry. A typical analysis requires 1 microL of sample solution and produces a CO2 peak approximately 5 s wide. The system can measure "bulk" delta13C values of approximately 10 nmol of organic carbon with precision better than 0.2 per thousand. For samples containing approximately 1 nmol of C, precision is approximately 1 per thousand. Precision and sensitivity are limited mainly by background noise derived from carbon within the wire. Instrument conditions minimizing that background are discussed in detail. Accuracy is better than 0.5 per thousand for nearly all dissolved analytes tested, including lipids, proteins, nucleic acids, sugars, halocarbons, and hydrocarbons. The sensitivity demonstrated here for 13C measurements represents a approximately 1000-fold improvement relative to existing elemental analyzers and should allow the use of many new preparative techniques for collecting and purifying nonvolatile biochemicals for isotopic analysis.
Sessions, Alex LSylva, Sean PHayes, John MengResearch Support, U.S. Gov't, Non-P.H.S.2005/10/15 09:00Anal Chem. 2005 Oct 15;77(20):6519-27.